Influences of tolfenamic acid and flunixin meglumine on the disposition kinetics of levofloxacin in sheep - Durna Corum, Duygu; Corum, Orhan; Yildiz, Ramazan; Eser Faki, Hatice; Ider, Merve; Cetin, Gul; Uney, Kamil (Akademiai Kiado Zrt., 2020)
AbstractThe pharmacokinetics of levofloxacin (4 mg/kg), administered both alone and in combination with tolfenamic acid (2 mg/kg) and flunixin meglumine (2.2 mg/kg), was established after intravenous administration in sheep. Plasma levofloxacin concentrations were assayed by high-performance liquid chromatography and analysed according to the two-compartment open model. Following the administration of levofloxacin alone, the mean distribution half-life, elimination half-life, total clearance, volume of distribution at steady state and area under the plasma concentration–time curve were 0.20 h, 1.82 h, 0.39 L/h/kg, 0.96 L/kg and 10.40 h × µg/mL, respectively. Tolfenamic acid and flunixin meglumine caused a slow elimination and increased plasma concentrations of levofloxacin in combination administration. Levofloxacin, with an alteration in the dosage regimen, can be used effectively with tolfenamic acid and flunixin meglumine for the therapy of infections and inflammatory conditions in sheep.
Keywords: Anti-Inflammatory Agents, Non-Steroidal; Levofloxacin; SV Veterinary science / állatorvostudomány; Anti-Bacterial Agents; Clonixin; Area Under Curve; Injections, Intravenous; Animals; ortho-Aminobenzoates; Sheep, Domestic; Half-Life; 3. Good health